2016
DOI: 10.1111/1744-7917.12301
|View full text |Cite
|
Sign up to set email alerts
|

Injury‐induced rapid activation of MAPK signaling in dechorionated eggs and larvae of the silkworm Bombyx mori

Abstract: Previous study showed that diapause in Bombyx mori eggs can be terminated by dechorionation and that activation in the mitogen-activated protein kinase (MAPK)/extracellular signal-regulated kinase (ERK) in dechorionated cultured eggs is involved in diapause termination. In the present study, the possible mechanism underlying activation of ERK upon dechorionation was further investigated. Results showed that mechanical injury of diapause eggs without medium incubation also resulted in rapid increase in the phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 40 publications
2
3
0
Order By: Relevance
“…In the present study, we found that dechorionation significantly increased insulin, and other growth factors (Buchon et al, 2014). Injury-induced rapid activation of MAPK signaling in dechorionated eggs and larvae of B. mori was also previously reported (Gu & Chen, 2017).…”
Section: Changes In Gene Expressions and Ecdysteroid Levels In Dechor...supporting
confidence: 88%
See 1 more Smart Citation
“…In the present study, we found that dechorionation significantly increased insulin, and other growth factors (Buchon et al, 2014). Injury-induced rapid activation of MAPK signaling in dechorionated eggs and larvae of B. mori was also previously reported (Gu & Chen, 2017).…”
Section: Changes In Gene Expressions and Ecdysteroid Levels In Dechor...supporting
confidence: 88%
“…In Drosophila , it is well documented that upon damage, intestinal regeneration is mediated by numerous factors including cytokines, insulin, and other growth factors (Buchon et al, 2014). Injury‐induced rapid activation of MAPK signaling in dechorionated eggs and larvae of B. mori was also previously reported (Gu & Chen, 2017). In addition, a previous study showed that U0126 at 100 µM inhibited EPPase gene expressions in dechorionated and incubated eggs (Fujiwara, Tanaka et al, 2006).…”
Section: Discussionsupporting
confidence: 76%
“…ERK is involved in important physiological processes in insects, including cell proliferation, differentiation, and resistance to apoptosis (Bonnefoy‐Berard et al, 2004), and is therefore essential in insect growth and development. It also regulates a range of physiological functions, such as growth and development (Fujiwara, Shindome, et al, 2006), reproduction (Guo et al, 2019), innate immunity (Lin & Gu, 2007), (Fujiwara, Shindome, et al, 2006; Guo et al, 2019; Lin & Gu, 2007), the synthesis of silk proteins (Ma et al, 2018), and diapause of eggs (Gu & Chen, 2017). Notably, the various cascade kinases involved in the activation of ERK also play unique roles in silkworms.…”
Section: Functions Of the Erk Pathway In Silkwormsmentioning
confidence: 99%
“…It also regulates a range of physiological functions, such as growth and development (Fujiwara, Shindome, et al, 2006), reproduction (Guo et al, 2019), innate immunity (Lin & Gu, 2007), (Fujiwara, Shindome, et al, 2006;Guo et al, 2019;Lin & Gu, 2007), the synthesis of silk proteins (Ma et al, 2018), and diapause of eggs (Gu & Chen, 2017). Notably, the various cascade kinases involved in the activation of ERK also play unique roles in silkworms.…”
Section: Functions Of the Erk Pathway In Silkwormsmentioning
confidence: 99%
“…Both the ERK- and JNK-dependent signaling pathways appear to contribute to Bombyx nucleopolyhedrovirus infection (Katsuma et al, 2007 ). More recently, we reported that JNK signaling together with other MAPK signaling pathways, which are rapidly induced by injury, are related to diapause termination in dechorionated Bombyx eggs (Gu and Chen, 2017 ).…”
Section: Introductionmentioning
confidence: 99%